2011
DOI: 10.1002/ange.201104193
|View full text |Cite
|
Sign up to set email alerts
|

An Organic Optical Transistor Operated under Ambient Conditions

Abstract: Aller guten Dinge sind drei: Die Hauptmerkmale eines optischen Transistors (Steuerung und Verstärkung) werden anhand der photophysikalischen Eigenschaften einer molekularen Triade gezeigt (siehe Bild). Zwei Bausteine der Triade sind hocheffiziente Fluorophore, wohingegen der dritte Baustein ein photochromes Molekül ist, das durch Licht reversibel von einer bistabilen Form in die andere umgewandelt werden kann.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Organic molecular switches may provide potential capability to applications in transmit, modulate and detect light or photons. Previous investigation of DTE derivatives indicates extreme potentials as all-optical transistors, whereas the fluorescence on/off ratio is not very high 7 .…”
Section: Q(t) Pmi-1dtementioning
confidence: 93%
See 1 more Smart Citation
“…Organic molecular switches may provide potential capability to applications in transmit, modulate and detect light or photons. Previous investigation of DTE derivatives indicates extreme potentials as all-optical transistors, whereas the fluorescence on/off ratio is not very high 7 .…”
Section: Q(t) Pmi-1dtementioning
confidence: 93%
“…Alternatively, fluorescent spectroscopy exhibiting high sensitivity provides another method to characterize the photoswitching properties of DTEs, which requires those DTEs that display both photochromism and fluorescence switching. Evidently, fluorescence switching is more promising than photochromism in all-optical switches and transistors [7][8][9] . A great deal of efforts have been taken to develop novel photoswitchable fluorescent DTE derivatives with high fluorescence quantum yields (F F ), on/off ratios and switching speeds [10][11][12][13][14][15][16] .…”
mentioning
confidence: 99%
“…This demonstrates the possibility of modulating the fluorescence emission from a single nitrogen-vacancy by up to 80% for this chosen green excitation power. Quenching of fluorescence could be obtained with other molecular species by means of alternative mechanisms such as conformational transformation in photochromic molecules 21,22 , although these are intrinsically much slower than the electronic response time of our system. Nevertheless, unlike molecules or quantum dots 11,13 , nitrogen-vacancy centres are stable and bright emitters, allowing us to observe this effect at room temperature and over a long time span 15,18 .…”
mentioning
confidence: 99%
“…Among the various excellent works, recently Pärs et al reported on the possibility to covalently tether an organic semiconducting molecule such a perylene bisimide (PBI) to a dithinylcyclopentene (DCP) [183]. The molecular system would act as an optical transistor operating under ambient conditions (Figure 7.4).…”
Section: Photochromic Molecules and Organic Semiconductors Incorporatmentioning
confidence: 99%